Peran Media Audio-Auvisual dalam Meningkatkan Kemampuan Bahasa Anak Usia Dini di TK Kusuma Cendekia - Fahimah Milatin Nada; Suryadi Suryadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Language skills are an important aspect in early childhood growth and development because they are the basis for building communication, developing mindsets, and interacting with others. The purpose of this study is to reveal the role of audio-visual media in supporting the improvement of early childhood language skills in Kusuma Cendekia Kindergarten. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The findings show that the use of audio-visual media, such as children's songs, educational animations, and illustrated stories, is able to encourage increased vocabulary mastery, fluency in speaking, and children's courage in communicating. The media is considered effective because it is able to present interesting, concrete, and interactive learning, and is in harmony with the developmental stage of children aged 5-6 years. Teachers also apply strategies such as singing together, role-playing, and retelling the content of the video to strengthen children's language mastery. Nonetheless, some obstacles were found, such as the limitations of facilities and challenges in selecting the right content. The results of this study recommend the use of audio-visual media as one of the creative and fun learning tools in the early childhood education environment.